Critical steps in the isolation and expansion of adipose-derived stem cells for translational therapy. (8th June 2015) - Riis, S.; Zachar, V.; Boucher, S.; Vemuri, M.C.; Pennisi, C. P.; Fink, T.
Abstract : Since the discovery of adipose-derived stem cells (ASCs), there have been high expectations of their putative clinical use. Recent advances support these expectations, and it is expected that the transition from pre-clinical and clinical studies to implementation as a standard treatment modality is imminent. However ASCs must be isolated and expanded according to good manufacturing practice guidelines and a basic assurance of quality, safety, and medical effectiveness is needed for authorisation by regulatory agencies, such as European Medicines Agency and US Food and Drug Administration. In this review, a collection of studies investigating the influence of different steps of the isolation and expansion protocol on the yield and functionality of ASCs has been presented in an attempt to come up with best recommendations that ensure potential beneficial clinical outcome of using ASCs in any therapeutic setting. If the findings confirm the initial observations of beneficial effects of ASCs, the path is paved for implementing these ASC-based therapies as standard treatment options.